Jab1/CSN5 mediates E2F dependent expression of mitotic and apoptotic but not DNA replication targets - Lu, Huarui (Landes Bioscience, 2011)
The E2F transcription factors are critical regulators of cell cycle and cell fate control. Several classes of E2F target genes have been categorized based on their roles in DNA replication, G(2)/M and mitosis, apoptosis, DNA repair, etc. How E2Fs coordinate the appropriate and timely expression of these functionally disparate gene products is poorly understood at a molecular level. We previously showed that the E2F1 binding partner Jab1/CSN5 promotes E2F1-dependent induction of apoptosis but not proliferation. To better understand how Jab1 regulates E2F1 dependent transcription, we performed gene expression analysis to identify E2F target genes most and least affected by shRNA depletion of Jab1. We find that a significant number of apoptotic and mitotic E2F target genes are poorly expressed in cells lacking Jab1/CSN5, whereas DNA replication genes are generally still highly expressed. Chromatin immunoprecipitation analysis indicates that both Jab1 and E2F1 co-occupy apoptotic and mitotic, but not DNA replication target genes. We explored a potential connection between PI3K activity and Jab1/E2F1 target gene induction, and found that E2F1/Jab1 co-induction of apoptotic target genes can be inhibited by activated PI3K. Furthermore, PI3K activity interferes with formation of the E2F1/Jab1 complex by co-immunoprecipitation. Jab1/CSN5 is upregulated in a variety of human tumors, but it’s unclear how its pro-proliferatory and apoptotic functions are regulated in this context. We explored the link between increased Jab1 levels and PI3K function in tumors and detected a highly significant correlation between elevated Jab1/CSN5 levels and PI3K activity in breast, ovarian, lung and prostate cancers.